Carbon emissions and non-biodegradable medical waste generation with alternative dosing strategies. Issue 28 (1st October 2022) - Jacobson, Sofia I; Kacew, Alec; Knoebel, Randall W.; Hsieh, Po-Hung; Ratain, Mark J.; Strohbehn, Garth William
Abstract : 44 Background: Climate change from human activity results in catastrophic environmental effects that endanger human life. Health care is responsible for ̃10% of greenhouse gas emissions in the United States, thus health systems are pursuing net-zero emissions care. Methods: This single-center, retrospective, case-control study evaluated the environmental impact of alternative trastuzumab, specifically reducing adjuvant therapy duration from 12 to 6 months (in line with clinical trial evidence) and changing administration frequency from every 3 to every 4 weeks (based on pharmacokinetic simulation). Carbon emissions were estimated from round-trip travel distances, and non-biodegradable waste was estimated by collecting and weighing all single-use items used in trastuzumab preparation and administration. We generated population estimates using SEER data. Results: We identified 192 patients with HER2+ breast cancer who received trastuzumab between 2017 and 2019. At a population level, the environmental impact of continued standard-of-care dosing was 22, 919 kg of waste and 1, 077, 210 kg of carbon emissions, requiring ̃49, 000 trees to offset. 12 versus 6 months adjuvant treatment duration led to larger expected environmental benefits: 50, 536 kg of waste and 3, 265, 039 kg of carbon emissions could be avoided with universal adoption of 6-month adjuvant therapy. Conclusions: Given health care's increasing emphasis on net-zero care, clinical trials and use of pharmcokinetically equivalent alternative dosing strategies can in part justified by environmental benefits.Estimated environmental footprint in the U.S. population of patients with HER2+ breast cancer receiving adjuvant trastuzumab using different dosing strategies. Non-Biodegradable Waste 12 Months Duration 6 Months Duration Excess Waste Production (kg) (Q3W for 12 mo Q4W for 6 mo) Q3W Waste (kg) (18 doses) Q4W Waste (kg) (13 doses) Q3W Waste (kg) (9 doses) Q4W Waste (kg) (7 doses) Patient 4.51 3.26 2.25 1.75 2.76 U.S. Population of HER2+ Breast Cancer Receiving Adjuvant Trastuzumab (N 18, 310) 82, 578 59, 691 41, 198 32, 043 50, 536 CO2 Emissions 12 Months Duration 6 Months Duration Q3W CO2 Emissions (kg) (18 doses) Q4W CO2 Emissions (kg) (13 doses) Q3W CO2 Emissions (kg) (9 doses) Q4W CO2 Emissions (kg) (7 doses) Excess CO2 Emissions (kg) (Q3W for 12 mo Q4W for 6 mo) # Trees to Offset Excess CO2 Median Patient 291.79 210.74 145.90 113.48 178.32 8 U.S. Population of HER2+ Breast Cancer Receiving Adjuvant Trastuzumab (N 18, 310) 5, 342, 675 3, 858, 649 2, 671, 429 2, 077, 819 3, 265, 039 149, 979